Specific Interactions Between Nipah Virus Nucleocapsid (N) Protein and Phospho-(P) Protein Using the Yeast Two-Hybrid System - Mohd. Mohidin, Taznim Begam (2006)
Nipah virus (NiV) which is a member of a new genus, Henipavirus, in the family Paramyxoviridae, encodes an unusually large phospho- (P) protein compared to other known paramyxoviruses. In this study, the region(s) involved in the interaction between this exceptionally large P protein with its nucleocapsid (N) protein was investigated in vivo using the yeast two-hybrid system. Deletion analysis was used to map the domain(s) of both the N and P proteins involved in N-P and P-N interactions. Mapping of the domains of N protein involved in its interaction with the P protein revealed that the Cterminal 30 amino acids (423-452 residues) are crucial for N-P interaction. However, mapping of the domains of P protein involved in the P-N association demonstrated that both the C-terminal 63 amino acids (470-532 residues) and the immediate N-terminal 62 amino acids (1-62 residues) simultaneously play a major role. Comparison of these findings with other studies indicates that paramyxoviruses are different in terms of interaction domains(s) between these two essential viral proteins involved in genome replication.